Patterns of clinical mentorship in undergraduate nurse education: A comparative case analysis of eleven EU and non-EU countries - Beata Dobrowolska; Ian Mcgonagle; Ros Kane; Christine Jackson; Barbara Kegl; Michael Bergin (2016)
Background: In spite of the number of studies available in the field and policy documents developed both at thenational and the international levels, there is no reliable data available regarding the variation of roles occupiedby clinical mentors (CMs) across countries.Objectives: To describe and compare the CM's role; responsibilities; qualifications; employment requirementsand experience in undergraduate nurse education as enacted in 11 European Union (EU) and non- EU countries.Design: A case study design.Participants and Setting: A panel of expert nurse educators from 11 countries within and outside of the EU(Croatia, Czech Republic, England, Iceland, Ireland, Italy, Poland, Serbia, Slovenia, Spain, and the USA).Methods: A questionnaire containing both quantitative and qualitative questions was developed and agreed bythe panel using a Nominal Group Technique (NGT); four cycles of data collection and analysis were conductedinvolving key experts in nursing education in each country.